Molecular epidemiology of dengue type 2 and 3 viruses in Sarawak and Vietnam - Ravindran, Thayan. (Universiti Malaysia Sarawak (UNIMAS), 2001)
Two methods were carried out to study the molecular epidemiology of Sarawak and Vietnam dengue type 2 and 3 viruses. In the first approach, sequencing of the envelope/non-structural 1 gene junction (E/NS1, 240-bp) was done to infer phylogenetic tree while restriction site-specific polymerase chain reaction was carried out as the second approach. Results from both the methods were compared.